Experimental study of dielectric properties of composite materials pozzolan/DGEBA - Irekti, Amar; Bezzazi, Boudjema; Smith, Agnès; Aribi, Chouaib (Polymer composites, 2017)
The subject of composite materials with reinforced filler has been studied recently. This study to improve both the dielectric and structural characteristics of diglycidyl ether of bisphenol a (DGEBA) focused on the appropriate use (from 5% to 60 wt%) of pozzolan filler mechanically grinded to obtain a very fine particle size (Ø < 10 μm) and area surface of 23.5 m2 g−1. The dielectric properties were investigated at great filler concentrations by weight. Epoxy microcomposite samples with a good dispersion of nanoparticles in the epoxy matrix were prepared and experiments were performed to measure the capacitance (C), the electrical resistance (R), and impedance (Z) as a function of frequency (1 kHz–10 kHz). Measurements were made using dielectric spectroscopy over the temperature range 25–80°C. Using the scanning electron microscope (SEM), the morphologies and structure of the surface and fracture surfaces of Pozzolan/DGEBA composites were observed. POLYM. COMPOS., 38:324–331, 2017. © 2015 Society of Plastics Engineers